THE IMPACT OF ROAD CONSTRUCTION SECTOR ON HOUSEHOLD INCOME INTRA AND INTER-REGION OF WEST-EAST INDONESIA - Slamet Muljono; Bonar M. Sinaga; Arief Daryanto; Max Antameng (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
The differences in interregional development have caused gaps in regions’ advancements and prosperity, such as in the case of Western Indonesia (WI) and Eastern Indonesia (EI) and between urban and rural areas. The objective of this study is to analyze the structural path of road infrastructure construction sector on household income distribution change in both Intra and Inter West-East Region of Indonesia. The model used is Interregional Social Accounting Matrix West and East Region of Indonesia (IRSAM WEI). Within the model framework, construction sector is disaggregated into construction of road infrastructure sector (including bridge) and other construction sector. Meanwhile, the urban and rural household income is disaggregated into low, medium and high income. The Structural Path Analysis (SPA) shows that the strongest multiplier effect comes from production factor of worker and capital before reaching households. Keywords : road construction sector, household income, Structural Path Analysis, Western region of Indonesia, Eastern region of Indonesia, Interregional Social Accounting Matrix